COVID-19 lockdown: housing built environment's effects on mental health. (30th September 2020) - Morganti, A; Brambilla, A; Amerio, A; Aguglia, A; Odone, A; Costanza, A; Signorelli, C; Serafini, G; Amore, M; Capolongo, S
Abstract: Background: Since the World Health Organization (WHO) declared the coronavirus infectious disease 2019 (COVID-19) outbreak a pandemic on March 11th, severe 'lockdown' measures have been adopted by the Italian Government. For over two months of stay-at-home, houses became the only place where people slept, ate, worked, practiced sports, and socialized. As consolidated evidence exists on housing as a determinant of health, it is of great interest to explore the impact that COVID-19 response-related lockdown measures had on mental health and wellbeing. Methods: We conducted a large web-based survey on 9261 subjects in Northern Italy, one of the Regions most heavily hit by the pandemic in Europe. Participants were recruited among university staff, faculty and students. The questions included socio-demographic features of the participants; international evaluation scales designed to recognize depressive-, anxiety- and sleep-related symptoms, impulsivity, quality of life; architectural parameters investigating housing physical characteristics. Results: As emerges from our analysis poor housing is associated with increased risk of depressive symptoms during lockdown. In particular, living in apartments < 60 m2, with poor quality view and indoor area is associated with, respectively, 1.31 (95CI), 1.368 (95CI), and 2.253 (95CI) time the risk of moderate/severe and severe depressive symptoms. Subjects reporting worsened working performance from home were over four times more likely to also report depression (OR = 4.28, 95%CI). Conclusions: Our findings suggest housing played a major role in influencing people mental health and wellbeing during COVID-19 pandemic. We argue strengthened multi-interdisciplinary approach involving urban planning, public mental health, environmental health, epidemiology, and sociology, is needed to inform the planning implementation and monitoring of housing policies centered on population health. Key messages: COVID-19 lockdown mitigation measures strongly impacted on Mental Health. Living in apartments < 60 m2, with poor quality view and indoor area significatively increase the risk of moderate and severe depressive symptoms.